DESAIN PERENCANAAN PEMBANGUNAN WILAYAH SECARA KOMPREHENSIF MELALUI PENDEKATAN ANALISIS LOKUS DAN FOKUS, DENGAN KASUS AKSELERASI PENCAPAIAN INDEK PEMBANGUNAN MANUSIA (IPM) DI KOTA BEKASI - Nandang Najmulmunir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2006)
The achievement of regional development goals are effected by several factors, one of them is the good regional plan. The Good regional plan is indicated by the identified location of the problems, namely Locus. And the identified problems, namely Focus. The Locus and Focus plan are useful for guidance for practices and calculating the limited financial resources. The Locus and Focus are useful too for integrated development regional program, in order to get the effectiveness of the problems solving